Impact of DLL3 Expression as Prognostic Factor in Extensive Stage of Small Cell Lung Cancer Treated With First‐Line Chemotherapy - Hohyung Nam; Soon‐Hee Jung; Jii Bum Lee; Jee Hyun Kong; Seungtaek Lim (Thoracic Cancer)
ABSTRACT Introduction Small cell lung cancer (SCLC) is known for its high proliferative rate and poor prognosis. Although Delta‐like ligand 3 (DLL3) is specifically expressed on the surface of SCLC, the association of DLL3 with prognosis in SCLC remains uncertain. Hence, we aimed to evaluate prognostic role of DLL3 in extensive stage of SCLC treated with first‐line chemotherapy. Materials and Methods A total of 54 patients with extensive stage of SCLC (ES‐SCLC) who were treated with first‐line chemotherapy were included for our analysis. In addition, tissue specimen should be available for immuno‐histochemical staining for DLL3, and their clinico‐pathologic data, including progression‐free survival (PFS) and overall survival (OS), were obtained. DLL3 expression and the percentage of tumor cells with DLL3 positive among total cancer cells were analyzed microscopically and DLL3 high and DLL3 low were defined as the percentage of DLL3 positive tumor cells versus total cancer cells ≧ 75% and < 75%, respectively. Results DLL3 expression was not associated with any of the clinico‐pathological characteristics such as age at diagnosis, sex, response to first‐line chemotherapy, second‐line chemotherapy (Yes or No), and number of metastatic sites. However, response to first‐line chemotherapy and number of metastatic sites were correlated to PFS, while DLL3 expression and number of metastatic sites were correlated to OS. Conclusion DLL3 was highly expressed in SCLC, and not associated with any clinico‐pathological characteristics. In survival outcome, DLL3 was correlated with worse OS, which suggests the prognostic role of DLL3 in ES‐SCLC.